In Silico and In Vitro Study Selaginella doederleinii Herb Extract as An Antineoplastic on MCF-7 Cells and Formulation Development of Nano Effervescent Granule - Anggraini, Chaessy Yori; Kusumaningtyas, Triana Arum; Juniananda, Melisa; Ningrum, Dhecella Winy Cintya; Febriansah, Rifki; Hermawansyah, Adi (Indonesian Journal of Cancer Chemoprevention, 2023)
Breast cancer, the leading cause of cancer-related deaths in women with 685,000 deaths in 2020. Exploring natural compounds with minimal side effects has emerged as a potential treatment. However, utilizing natural substances faces challenges, such as poor bioavailability, requiring technologies like nanotechnology to enhance absorption. This study focuses on evaluating Ethanol Extract of Selaginella doederleinii (EESD) as an anticancer against MCF-7, both in silico, in vitro methode and develop a formulation of EESD nanoparticle effervescent granules. This study commenced with extraction, Gas Chromatography-Mass Spectrometry (GC-MS) identification, in silico studies, namely bioinformatics and molecular docking, 3-(4,-5-dimethylthiazo-2-yl)-2,5-diphenyltetrazolium bromide (MTT) Assay tests on MCF-7, and the formulation of nanoparticle preparations. EESD was extracted using the maceration method, resulting in an extract weighing 103.5 grams with a 6.9% yield. GC-MS identified three major compounds—cyclopentadecanoic, 2-hydroxy; hexadecanoic acid; and 9-octadecanoid, methyl ester. Bioinformatics revealed interactions with specific protein targets, and molecular docking indicated hexadecanoic acid's superior binding to TP53, surpassing paclitaxel at -8.7 kcal/mol. This suggests its potential to modulate TP53, impacting P53's role in impeding cancer cell growth. EESD exhibited an IC50 of 215μg/mL, signifying moderate cytotoxicity. In formulating nanoparticle effervescent granules, five formulas were transformed into nanoparticles and underwent organoleptic, pH, granule dissolution, and water content evaluations. Formula I is the formula that best meets the criteria with a pH of 6.55, granule dissolution <5 minutes, and water content <4%. The research results indicate that EESD shows anticancer activity against MCF-7 and this study has successfully developed a formula of nanoparticle from EESD in effervescent granule form.Keywords: Selaginella doederleinii, breast cancer, co-Cemotheraphy, MCF-7 Cell, in silico.